Plant Growth Promoting Rhizobacteria for Biocontrol of Tomato Bacterial Wilt Caused by Ralstonia solanacearum - Habtamu Mekonnen; Mulugeta Kibret; Fassil Assefa (International Journal of Agronomy)
Bacterial wilt induced by Ralstonia solanacearum is one of the most damaging and widespread diseases of tomatoes in the world. Biological control with rhizobacteria is one of the efficient components of integrated pest management methods used to control the disease and enhance production. To this end, plant growth-promoting rhizobacteria (Bacillus isolate BDUA1, and Pseudomonas isolates BBDUA2 and BDUA3) isolated from the tomato rhizosphere were evaluated for their plant growth-promoting traits using standard methods, and selected isolates were also tested for their biocontrol efficacy on tomato bacterial wilt disease under greenhouse conditions. All isolates produced cellulase and lipase, and only BDUA1 and BDUA3 produced protease and amylase. Besides, BDUA1 and BDUA2 showed phosphate solubilization and production of indole-3-acetic acid, HCN, and siderophore, while BDUA3 solubilized phosphate and produced HCN and siderophore. Our results showed that BDUA1 and BDUA2 reduced bacterial wilt incidence on the Maya variety by 51.9% and 48.5%, respectively, and on the Melkesalsa variety by 51.8% and 48.5%, respectively. Treatment of the Melkesalsa variety with BDUA1 displayed the highest height (36.91 cm), followed by treatment with BDUA2 (31.74 cm) on the same variety. BDUA1 induced the highest effect on increasing the dry weight of shoots and roots by 4.16 g and 0.59 g in the Maya variety and in the Melkesalsa variety by 3.63 g and 0.48 g, respectively. Similarly, BDUA2 had the greatest effect on increasing the dry weight of shoots and roots by 3.8 g and 0.54 g of the Maya variety and on the Melkesalsa variety by 3.12 g and 0.41 g, respectively. The overall result showed that BDUA1 and BDUA2 could be used as promising plant growth promotion and biocontrol agents for the management of tomato bacterial wilt disease provided they were validated under field conditions.